Evolution of checkpoint inhibitors for the treatment of metastatic gastric cancers: Current status and future perspectives. (May 2018) - Taieb, Julien; Moehler, Markus; Boku, Narikazu; Ajani, Jaffer A.; Yañez Ruiz, Eduardo; Ryu, Min-Hee; Guenther, Silke; Chand, Vikram; Bang, Yung-Jue
Highlights: Treatment of advanced gastric cancers remains an area of great unmet need. Anti–PD-1/PD-L1 antibodies have shown clinical activity in gastric cancers. Phase 3 trials are assessing anti–PD-1/PD-L1 monotherapy and combination regimens. First-line, maintenance, and later-line treatment strategies are being evaluated. Anti–PD-1 agents have received initial approvals for later-line treatment. Abstract: Background: Standard treatment options for patients with advanced gastric or gastroesophageal junction cancer (GC/GEJC) are associated with limited efficacy and some toxicity. Recently, immunotherapy with antibodies that inhibit the programmed death 1 (PD-1)/programmed death ligand 1 (PD-L1) interaction has emerged as a new treatment option. This manuscript reviews early-phase and late-phase trials of immunotherapy in advanced GC/GEJC. Methods: Searches for studies of immunotherapy in GC/GEJC were performed using PubMed, ClinicalTrials.gov, and abstract databases for select annual congresses. Findings were interpreted based on expert opinion. Results: Monotherapy with anti–PD-1/PD-L1 antibodies, including pembrolizumab, nivolumab, avelumab, durvalumab, and atezolizumab, has shown interesting objective response rates (ORRs; 7–26%) across varying GC/GEJC populations, with ORRs potentially higher in PD-L1 + vs PD-L1 − tumors. Safety profiles compare favorably with chemotherapy, with grade ≥3 treatment-related adverse events occurring in 5–17%. Based on a large phase 2 study, pembrolizumab was approved in the United States for third-line treatment of patients with PD-L1 + GC/GEJC. In a phase 3 trial, third-line or later nivolumab increased overall survival vs placebo in an Asian population, leading to regulatory approval in Japan, although other completed phase 3 trials did not show superiority for pembrolizumab or avelumab monotherapy vs chemotherapy. Other trials in advanced GC/GEJC are assessing various anti–PD-1/PD-L1–based strategies, including administration in first-line and later-line settings and as combination (with chemotherapy or agents targeting other immune checkpoint proteins, eg, CTLA-4, LAG-3, and IDO) or switch-maintenance regimens. Conclusions: Anti–PD-1/PD-L1 antibodies have shown encouraging clinical activity in advanced GC/GEJC. Results from ongoing phase 3 trials are needed to further evaluate the potential roles of these agents within the continuum of care.